Psyllium reduces inulin-induced colonic gas production in IBS: MRI and in vitro fermentation studies. Issue 5 (5th August 2021) - Gunn, David; Abbas, Zainab; Harris, Hannah C; Major, Giles; Hoad, Caroline; Gowland, Penny; Marciani, Luca; Gill, Samantha K; Warren, Fred J; Rossi, Megan; Remes-Troche, Jose Maria; Whelan, Kevin; et al.
Abstract : Objective: Health-promoting dietary fibre including inulin often triggers gastrointestinal symptoms in patients with IBS, limiting their intake. Our aim was to test if coadministering psyllium with inulin would reduce gas production. Design: A randomised, four-period, four-treatment, placebo-controlled, crossover trial in 19 patients with IBS. Subjects ingested a 500 mL test drink containing either inulin 20 g, psyllium 20 g, inulin 20 g+ psyllium 20 g or dextrose 20 g (placebo). Breath hydrogen was measured every 30 min with MRI scans hourly for 6 hours. Faecal samples from a subset of the patients with IBS were tested using an in vitro fermentation model. Primary endpoint was colonic gas assessed by MRI. Results: Colonic gas rose steadily from 0 to 6 hours, with inulin causing the greatest rise, median (IQR) AUC(0–360 min) 3145 (848–6502) mL·min. This was significantly reduced with inulin and psyllium coadministration to 618 (62–2345) mL·min (p=0.02), not significantly different from placebo. Colonic volumes AUC(0–360 min) were significantly larger than placebo for both inulin (p=0.002) and inulin and psyllium coadministration (p=0.005). Breath hydrogen rose significantly from 120 min after inulin but not psyllium; coadministration of psyllium with inulin delayed and reduced the maximum increase, AUC(0–360 min) from 7230 (3255–17910) ppm·hour to 1035 (360–4320) ppm·hour, p=0.007. Fermentation in vitro produced more gas with inulin than psyllium. Combining psyllium with inulin did not reduce gas production. Conclusions: Psyllium reduced inulin-related gas production in patients with IBS but does not directly inhibit fermentation. Whether coadministration with psyllium increases the tolerability of prebiotics in IBS warrants further study. Trial registration number: NCT03265002 .